The Virulence-Related MYR1 Protein of Toxoplasma gondii as a Novel DNA Vaccine Against Toxoplasmosis in Mice - Zheng, Bin; Ding, Jianzu; Lou, Di; Tong, Qunbo; Zhuo, Xunhui; Ding, Haojie; Kong, Qingming; Lu, Shaohong (Frontiers in Microbiology, 2019)
ABSTRACT Toxoplasma gondii causes serious public health problems, but there is no effective treatment strategy against it currently. DNA vaccines have shown promising findings in this regard. MYR1 is a new virulence factor identified in T. gondii that may have potential as a DNA vaccine candidate. We constructed a recombinant eukaryotic plasmid, pVAX1-MYR1, as a DNA vaccine, injected it intramuscularly into BALB/c mice, and evaluated its immunoprotective effects. pVAX1-MYR1 immunization induced a sequential Th1 and Th2 T-cell response, as indicated by high levels of Th1 and mixed Th1/Th2 cytokines at 2 and 6 weeks after immunization, respectively. These findings were corroborated by the antibody assays too. In addition, increased levels of antigen-specific lymphocyte proliferation, CD4+ and CD8+ T lymphocytes, cytotoxic T lymphocyte activity and cytokine (IFN-γ, IL-12, and IL-10) production were also observed in the immunized mice. These findings showed that pVAX1-MYR1 stimulated humoral and cellular immune responses in the immunized mice. The increased production of IFN-γ and IL-12 was correlated with increased expression of the T-bet and p65 genes of the NF-κB pathway. However, no significant increase was observed in the level of IL-4. The survival of mice immunized with pVAX1-MYR1 was also significantly prolonged compared with the control group mice. Based on all the above findings, the current study proposes that pVAX1-MYR1 can induce a T. gondii-specific immune response and should therefore be considered as a promising vaccine candidate against toxoplasmosis. To the best of our knowledge, this is the first report to evaluate the immunoprotective value of an MYR1-based DNA vaccine against T. gondii.